PENGARUH BEBERAPA CARA KEMATIAN IKAN TERHADAP MUTU IKAN KAKAP (Lutjanus sp.) - Reo, Albert R (Sam Ratulangi University, 2010)
The handling of fishery products play an important role in exploiting fisheries production, which began handling the treatment of fish caught, on board, when landed, the market-the market, retailers get to the processing plant. Storage temperature of fish plays an important role when the fish die. the use of low temperatures around 0oC after dead fish can extend the seizures (rigor mortis), lower enzymatic activity, bacterial, chemical and physical changes that can prolong the durable power of fish. How to fish death during arrest have a major influence on the process begins and the end of rigor mortis is consequential to the quality and durable power of fish. This study aims to determine the influence of how the death of fish on fish lasting power during cold storage. benefits of this research can provide information on the manner of death a good fish. Research results snapper fitness level based on organoleptic testing with scores ranging between 4.8 to 50 with an average rating of 50, 45.7, 38.5, 26.2 for treated fish were injected / gancu, 50, 38.1, 10, 5.4 for fish a dead flounder. Research results snapper fitness level based on the value-K test is: 25.78% injection treatment / gancu, 48.99% hit with a wood treatment on the head and the dead fish flounder 50.34%. Fish snapper (Lutjanus sp.) who was arrested dikaramba Likupang waters, the organoleptic and value-K is still suitable for consumption and for processing raw materials.